The Challenges in Product Design and Development in Project Management towards IR4.0 - Othman, Mohd Hilmi; Bamasood, Mohammed (Journal of Advanced Mechanical Engineering Applications, 2021)
This paper provides a review about the challenges in product design and development (PDD) in the context of the Industrial Revolution 4.0 (IR 4.0), with a particular focused on the problems that may be encountered by the project management (PM) team in the PDD phase. In recent decades, there has been a large number research, design, and development studies related to IR 4.0, such as synthesizing the applications of Big Data, Internet of things (IoT), Cloud Computing, Cybersecurity, and Artificial Intelligence. The effect of this revolution in technology is changing rapidly with new models and methods of manufacturing that have been proposed for the new future. The pandemic Covid-19 also accelerates the interest in using all kinds of online technology. However, to adapt and achieve the benefits of this revolution, industry players have to encounter several issues related to the PM, especially during the PDD phase. The management challenges discussed in this study were divided into four categories: the project team member selection, team leader selection, identifying potential customers, and design for the environment. In addition, some of the solutions and recommendation has been described using several examples.